The Geography of Environmental Crime: Conservation, Wildlife Crime and Environmental Activism - Potter, Gary R.; Nurse, Angus; Hall, Matthew (Palgrave Studies in Green Criminology, 2016)
This book critically examines both theory and practice around conservation crimes. It engages with the full complexity of environmental crimes and different responses to them, including: poaching, conservation as a response to wildlife crime, forest degradation, environmental activism, and the application of scientific and situational crime prevention techniques as preventative tools to deal with green crime. Through the contributions of experts from both the social and ecological sciences, the book deals with theoretical and practical considerations that impact on the effectiveness of contemporary environmental criminal justice. It discusses the social construction of green crimes and the varied ways in which poaching and other conservation crimes are perceived, operate and are ideologically driven, as well as practical issues in environmental criminal justice. With contributions based in varied ideological perspectives and drawn from a range of academic disciplines, this volume provides a platform for scholars to debate new ideas about environmental law enforcement, policy, and crime prevention, detection and punishment.